An Assessment of xsBa Flux as a Paleoproductivity Indicator and Its Water‐Depth Dependence in the Easternmost Equatorial Pacific Ocean. Issue 12 (1st December 2020) - Singh, Ajay K.; Marcantonio, Franco; Lyle, Mitchell
Abstract: We present the first regional‐scale records of biogenic Barium (xsBa) fluxes in the Panama basin of the eastern‐equatorial margin of the Pacific Ocean in order to assess xsBa as a paleoproductivity proxy. Measurements of xsBa from 13 cores that range in water depths from about 700 to 3, 000 m show an increase in 230 Th‐normalized xsBa mass accumulation rates (MARs) with increasing water depth during both marine oxygen isotope stages (MIS) 1 and 2. The correlation of xsBa MARs with depth are strong despite differences in bulk sediment MARs and differing degrees of sediment redistribution. We interpret the increasing xsBa with water depth as likely due to the continued decomposition and remineralization of falling and/or resuspended biogenic particles. xsBa does not seem to be affected by diagenetic sulfate reduction in most of the cores. Calculated estimates of xsBa preservation in the sediment pile are high and fluctuate between 45% and 52% throughout the last 25 kyr. Although xsBa fluxes can be a robust indicator of paleoproductivity, caution is needed if (a) there is evidence of sulfate reduction in sediments being analyzed, and (b) one is trying to quantify differences in paleoproductivity among sites that are located at different depths in the water column. Key Points: Strong positive correlation exists between water depth and xs 230 Th‐derived xsBa fluxes despite hydrographic and productivity differences Continued formation of xsBa in the water column best explains the observed depth dependence in xsBa The fidelity of xsBa fluxes as a productivity indicator in focused areas of the ocean floor seems to be maintained